Identifying the core concepts of pharmacology education: A global initiative. (3rd January 2023) - White, Paul J.; Guilding, Clare; Angelo, Tom; Kelly, John P.; Gorman, Laurel; Tucker, Steven J.; Fun, Ashleigh; Han, Jae; Chen, Guanliang; Samak, Yassmin; Babey, Anna‐Marie; Caetano, Fabiana A.; et al.
Abstract : Background and Purpose: In recent decades, a focus on the most critical and fundamental concepts has proven highly advantageous to students and educators in many science disciplines. Pharmacology, unlike microbiology, biochemistry, or physiology, lacks a consensus list of such core concepts . Experimental Approach: We sought to develop a research‐based, globally relevant list of core concepts that all students completing a foundational pharmacology course should master. This two‐part project consisted of exploratory and refinement phases. The exploratory phase involved empirical data mining of the introductory sections of five key textbooks, in parallel with an online survey of over 200 pharmacology educators from 17 countries across six continents. The refinement phase involved three Delphi rounds involving 24 experts from 15 countries across six continents. Key Results: The exploratory phase resulted in a consolidated list of 74 candidate core concepts. In the refinement phase, the expert group produced a consensus list of 25 core concepts of pharmacology. Conclusion and Implications: This list will allow pharmacology educators everywhere to focus their efforts on the conceptual knowledge perceived to matter most by experts within the discipline. Next steps for this project include defining and unpacking each core concept and developing resources to help pharmacology educators globally teach and assess these concepts within their educational contexts. Abstract :